Reproductive Traits in Berari Goats of Vidharbha Region of Maharashtra - Kale, Vaijnath B; Pawshe, Chaitanya H; Ingawale, Mahesh V; Deshmukh, Shyam G; Thorat, Milind G; Waghmare, Sunil P (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The objective of this study was to examine the different benchmarks of reproductive traits in Berari goats. The Berari goat was recentlyrecognised as India’s 23rd goat breed at the national level. The study was carried out for 18 months on 12 female Berari goat kids. Thedifferent benchmarks of reproductive traits observed non-significant difference in single and twins born kids such as age at puberty,age at maturity, duration of estrus, average weight at conception, age at kidding, time required for kidding and gestation length, whichwere found within normal range for the other breeds of goat. It was concluded that the Berari goat breed has lower age at first estrus,age at first kidding and higher reproductive performance, which can be exploited for improving the breeding efficiency of local nondescript goat population.
Keywords: Berari goat; Estrus; , Gestation; Puberty; Reproductive traits.